Crude Oil Induced Oxidative Changes and Chemoprotective Roles of Ocimum gratissimum and Gongronema latifolium Formulated Diet - Ujowundu, Cosmas; R.N, Nwaoguikpe; G.N, Okwu; A.C, Ene (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
The antioxidant and hepatoprotective effects of Ocimum gratissimum and Gongronema latifolium formulated diet were evaluated in crude petroleum oil induced toxicity in rats. Exposure to crude oil caused significant (p<0.05) decrease in superoxide dismutase, glutathione peroxidase, reduced glutathione and increase malondialdehyde. Hepatocyte damage was indicated by the rise in aspartate aminotransferase, total bilirubin and fluctuations in other liver parameters. However, the group intoxicated and fed simultaneously with the formulated diet showed some level of stability and modification in the evaluated biochemical parameters, indicating potential therapeutic and protective role of O. gratissimum and G. latifolium. Thyroid hormones and lipid profile were also determined.